Sertraline versus other antidepressive agents for depression. - Cipriani, A; La Ferla, T; Furukawa, T; Signoretti, A; Nakagawa, A; Churchill, R; McGuire, H; Barbui, C (2010)
BACKGROUND: The National Institute for Health and Clinical Excellence clinical practice guideline on the treatment of depressive disorder recommended that selective serotonin reuptake inhibitors should be the first-line option when drug therapy is indicated for a depressive episode. Preliminary evidence suggested that sertraline might be slightly superior in terms of effectiveness. OBJECTIVES: To assess the evidence for the efficacy, acceptability and tolerability of sertraline in comparison with tricyclics (TCAs), heterocyclics, other SSRIs and newer agents in the acute-phase treatment of major depression. SEARCH STRATEGY: MEDLINE (1966 to 2008), EMBASE (1974 to 2008), the Cochrane Collaboration Depression, Anxiety and Neurosis Controlled Trials Register and the Cochrane Central Register of Controlled Trials up to July 2008. No language restriction was applied. Reference lists of relevant papers and previous systematic reviews were hand-searched. Pharmaceutical companies and experts in this field were contacted for supplemental data. SELECTION CRITERIA: Randomised controlled trials allocating patients with major depression to sertraline versus any other antidepressive agent. DATA COLLECTION AND ANALYSIS: Two review authors independently extracted data. Discrepancies were resolved with another member of the team. A double-entry procedure was employed by two reviewers. Information extracted included study characteristics, participant characteristics, intervention details and outcome measures in terms of efficacy (the number of patients who responded or remitted), acceptability (the number of patients who failed to complete the study) and tolerability (side-effects). MAIN RESULTS: A total of 59 studies, mostly of low quality, were included in the review, involving multiple treatment comparisons between sertraline and other antidepressant agents. Evidence favouring sertraline over some other antidepressants for the acute phase treatment of major depression was found, either in terms of efficacy (fluoxetine) or acceptability/tolerability (amitriptyline, imipramine, paroxetine and mirtazapine). However, some differences favouring newer antidepressants in terms of efficacy (mirtazapine) and acceptability (bupropion) were also found. In terms of individual side effects, sertraline was generally associated with a higher rate of participants experiencing diarrhoea. AUTHORS' CONCLUSIONS: This systematic review and meta-analysis highlighted a trend in favour of sertraline over other antidepressive agents both in terms of efficacy and acceptability, using 95% confidence intervals and a conservative approach, with a random effects analysis. However, the included studies did not report on all the outcomes that were pre-specified in the protocol of this review. Outcomes of clear relevance to patients and clinicians were not reported in any of the included studies.